European Bioanalysis Forum recommendation: scientific validation of quantification by accelerator mass spectrometry. (November 2012) - Higton, David; Young, Graeme; Timmerman, Philip; Abbott, Richard; Knutsson, Magnus; Svensson, Leif D
Accelerator mass spectrometry (AMS) is being used more widely to provide PK data for early decision making or to generate absolute bioavailability data in later phases of development. Presently, there is no clear consensus on the level of the scientific validation required for these assays. The European Bioanalysis Forum (EBF) has conducted two surveys with its members and presented the results at its 4th Open Symposium. With AMS being used for discrete scientific assessment, method establishment of AMS assays should focus on science rather than trying to fit the assay parameters into validation criteria used for Regulated Bioanalysis guidance, and an amount of freedom of execution and interpretation is needed. Hence, the EBF focuses their recommendation on introducing terminology around scientific qualification or validation to be used in relation to AMS. Guidance is given on which parameters should be investigated when a qualified method is required. The recommendations of the EBF for scientific validation are described herein. The scientific validation of AMS assays will be different to that applied for LC–MS/MS assays, and an example is that accuracy and precision limits, as used for ligand-binding assays, would be more appropriate.